HAMBATAN HUKUM DALAM PELAKSANAAN PENDAFTARAN TANAH SECARA SPORADIK HAK ATAS TANAH ULAYAT (STUDI KASUS DI KELURAHAN KOTA NDORA) - Songku, Meyke Putri Basilia; Aloysius, Sukardan; Pello, Helsina F (Petitum Law Journal, 2024)
Customary land is one form of land ownership that is carried out jointly, customary rights as a legal technical term is a right that is inherent as a competence of rights in customary law communities in the form of authority / power to manage and regulate the land as well as its inward and outward practices. The ulayat rights of customary law communities are regulated in Article 3 of Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles, hereinafter referred to as UUPA. The research method uses the type of empirical legal research, namely data obtained directly from the results of interviews and observations. The results of the research and discussion show that: (1) General description of Kota Ndora village, Borong sub-district, East Manggarai Regency. (2) History of the division of Liang Bala customary land. (3) There are inhibiting factors in the implementation of sporadic land registration on customary land liang bala in Kota Ndora Village. (4) How efforts are made to overcome these obstacles in the implementation of customary land registration. The land registration process is carried out in the first time land registration activities sporadically, but in the process it cannot be said to be perfectly successful.